Current status and variation trend of seagrass beds in coastal water of Son Tra peninsula, Da Nang city - Nguyen Xuan, Hoa; Nguyen Nhat , Nhu Thuy; Nguyen Trung , Hieu (Vietnam Journal of Marine Science and Technology, 2021)
Species composition of seagrasses in coastal water of Son Tra peninsula was less diverse, with three species identified. Halophila ovalis was dominant. The seagrass beds are mainly distributed in Bai Nom and Bai But, with a total area of about 1 ha. The seagrass beds had been seriously degraded in both size and structure. Approximately 9 ha of seagrass beds (90% of total area) disappeared compared with data of 2005. Halophila ovalis had only been distributed at a depth of 2–3 m. Coverage, shoot density, and biomass of seagrass beds had also decreased.